The psychological impact on women during matchmaking process in arranged marriage (Rajarshi Janak University Research Journal, 2024)
This study examines the psychological impact of the matchmaking process in arranged marriage on women in the Dhanusha district of Nepal. The research used a semi-structured interview to explore the experiences of 100 women aged 20-40 who faced evaluation during the arranged marriage matchmaking process. The findings reveal that physical appearance, particularly skin complexion, and height, is a predominant standard in bride selection, often leading to reduced self-esteem, psychological distress, and feelings of insufficiency among women who do not conform to these societal expectations. Dowry remains a significant factor in urban and rural settings adding financial and emotional burdens on women and their families. Although educational qualification offers some agency in marriage negotiations, it does not alleviate the issues related to beauty standards and dowry demands. Proficiency in domestic skills is also appreciated, particularly in traditional rural settings where educational qualification is less valued. The research contributes to the knowledge of how deeply rooted cultural and traditional norms perpetuate gender inequality and adversely affect women's mental well-being. However, the study's limited sample size and geographical region suggest the need for further research across diverse regions to gain more comprehensive insights.